Norwegian pre-service teachers' understanding of reflective rehearsals and democratic citizenship education: opportunities and challenges - Sigrid Haukanes (Springer, 2024)
Abstract Implementing democratic citizenship across disciplines in education requires careful consideration of how pre-service teachers are prepared to translate this concept into classroom practice. This study investigates Norwegian pre-service teachers' understanding of reflective rehearsals as a model in teacher education for enhancing awareness of democratic citizenship education. Findings from focus group interviews with 24 participants reveal some opportunities offered by reflective rehearsals as a model for bridging theory and practice in teacher education. Reflective rehearsals are understood as a safe space for making fruitful errors, attempting change and developing professional judgement. Pre-service teachers express an increasing sense of ownership over their formation as becoming teachers. However, certain challenges are also discussed. Firstly, understanding democratic citizenship primarily as individual knowledge is problematic in teacher education, as it may separate pre-service teachers' knowledge from their experience. Secondly, explicit dialogue concerning the connection between practice and educational purposes is needed. This article argues that reflective rehearsals could become a foundation for exploring the intersection of practice, theory and purpose, if this connection is made explicit and framed critically in teacher education.